Local Government Involvement in Participatory Development on Simpor Applications as Monitoring Media for Physical Development in East Belitung Regency - Yuriati, Elva; Sakir, Sakir (ARISTO, 2022)
This study aims to determine the involvement of local government in participatory development through the Participatory Development Monitoring System Application (SIMPOR) in East Belitung Regency. The local government in this case is the OPD and the village government within the East Belitung Regency Government. This study uses a qualitative method with a case study approach. Data were obtained through interviews and literature study where the interview results were analyzed using Nvivo 12Plus software through the crosstab query feature. The results of the study show that: 1) the creation of the Simpor Application as a participatory development monitoring medium in East Belitung Regency has fulfilled the basics of developing government digitization; 2) the involvement of the village government in the Simpor Application, namely as community representatives who monitor and report development progress, especially by the village simpor admin; 3) the leading sector (Ekbang) as a third party acts as a verifier that bridges the village government with the OPD; 4) each OPD inputs information related to the development package and responses related to monitoring carried out by the village government into the Simpor application. The conclusion is that there is local government involvement in participatory development through the Simpor Application as an e-monev medium for physical development in the form of two-way monitoring that occurs in the monitoring process on the Simpor Application. In addition, there are several obstacles encountered in the implementation process of the Simpor Application, namely: 1) the development of the Simpor Application is still slow; and 2) the implementing human resources are still limited. Suggestions for the government of East Belitung Regency to expand involvement in the Simpor Application include: 1) the leading sector, in this case through the village government, it is better to start providing education or introduction of the Simpor Application to the community gradually; 2) the leading sector should recruit special human resources who have basic IT to develop Simpor Applications so that the performance provided is more optimal; and 3) the leading sector should increase the human resources of operators in charge of verification.